1984
DOI: 10.1016/0014-5793(84)80085-x
|View full text |Cite
|
Sign up to set email alerts
|

Do hydrophobic sequences cleaved from cellular polypeptides induce membrane fusion reactions in vivo?

Abstract: The concept that a direct interaction between Ca2+ and phospholipids is a major factor in membrane fusion reactions is questioned. Attention is drawn to a number of findings on associations between fusion and the proteolysis of membrane proteins. It is proposed that hydrophobic polypeptides, which are functionally comparable to the fusogenic proteins of certain viruses but which are produced in cells by the endogenous proteolysis of membrane and cellular proteins, may induce membrane fusion reactions in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 84 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…The polymorphism accessible to PtdEtn-containing membranes can be a powerful agent for inducing the initial destabilization of the apposed bilayers, but for fusion additional factors (25) are required.…”
Section: Methodsmentioning
confidence: 99%
“…The polymorphism accessible to PtdEtn-containing membranes can be a powerful agent for inducing the initial destabilization of the apposed bilayers, but for fusion additional factors (25) are required.…”
Section: Methodsmentioning
confidence: 99%
“…A role for soluble proteolytic enzymes in fusion processes is suggested by recent observations that limited proteolysis can initiate erythrocyte fusion (Lucy, 1984a). Lucy (1984b) has also proposed that hydrophobic polypeptides produced by proteolysis may induce membrane fusion. Couch & Strittmatter (1984) have now shown that the specific blockers of myoblast fusion that inhibit proteinases act on a cytosolic protein with an apparent Mr of 80000.…”
Section: Surface Biochemistry Of Myoblasts During Fusionmentioning
confidence: 99%
“…Serum albumin might also exert its effect on the AR by perturbing lipid bilayers of the cell membrane through its hydrophobic nature, as suggested by Lucy (1984) to explain how hydrophobic sequences cleaved from cellular polypeptides may induce membrane fusion. In view of Lucy's idea, it is of interest that Garcia et al (1984) have shown that the fusion of small unilamellar vesicles can be induced by a 9,000-molecular -weight fragment of serum albumin.…”
Section: Serum Albuminmentioning
confidence: 99%
“…Lucy (1984) reviewed evidence showing associations between membrane fusion and the action of proteases on membrane proteins and proposed that hydrophobic polypeptides (which he compared to fusogenic proteins of some viruses) produced by cellular proteases induce membrane fusion. Lucy also suggested that these hydrophobic polypeptides "perturb" the lipid bilayers of the cells resulting in fusion of membranes.…”
Section: Hydrolytic Enzymesmentioning
confidence: 99%